Pengaruh Penambahan Konsentrasi Puree Sirsak Terhadap Sifat Organoleptik Saus Manis Kue Patola - Hidayati, Chofifah Nur; Afifah, Choirul Anna Nur; Sutiadiningsih, Any; Bahar, Asrul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Patola cake is a traditional cake served with a sweet sauce combining brown sugar and coconut milk. The addition of soursop puree to sweet sauce is an innovation to add flavor to sauce products.The aim of this research is to find out; 1) The effect of adding soursop puree concentration on the organoleptic properties of patola cake sugar sauce. 2) The level of people's liking for the combination of patola cake and sugar sauce with the concentration of adding soursop puree. This type of research is experimental research which consists of one factor with the independent variable adding three treatments of soursop puree, namely: 25%, 30% and 40%. The dependent variables are viscosity, taste, aroma and color. The data collection technique uses an observation method in the form of a checklist using Google forms which is assessed by 30 people including training and semi-training panelists. Statistical analysis test using one way anova and further Duncan test. The research was conducted within the Culinary Education Study Program, Surabaya State University. The research results show; 1) there is no influence on color (0.13), viscosity (0.21 for sauce with a significance level above 0.05. 2) there is an influence on aroma (.00), taste (.002), liking (.002) on sauce with a significance level below 0.05.